Is Every Theory about Photography a Critical Action? Looking at the Book “Photography: A Critical Introduction” - Mohammad Khodadadi Motarjemzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This essay is trying to analyze and review the book, according to determined measures. This book has valuable, comprehensive, and new information about contemporary photography theories. Authors in every section focused on the special subject. The book includes seven main sections and a thorough appendix. Reviewing this book indicates that the book has been successful in paying close attention to recent discussions in photography theories. Giving references to credible references adds to the richness and validity of the book. Most sections are very useful for teaching courses of photography theory in university. Moreover, the translation of this book to Persian language is reliable. Every section of the book does not depend on another section, so every section can be regarded as a book. At last, the book deals with the description of the theories rather than the critique of ideas.